2015
DOI: 10.1186/s12978-015-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health beliefs and practices of female immigrants in Spain: a qualitative study

Abstract: BackgroundSexuality and reproduction are two areas that have been dealt with differently over time and across cultures. Immigrant women resident in Spain, are largely of childbearing age and have some specific needs. Female immigrants have specific beliefs and behaviors which may influence how they approach to the Spanish sexual and reproductive health services. There is less visibility of the health problems presented by women immigrants. This article aims to shed light on the sexual and reproductive health b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
2
21
0
3
Order By: Relevance
“…Structural racism as manifest in ideologies, practices, processes and institutions that operate to produce and reproduce differential access to power [13] is deeply enrooted in social institutions, including the health system, its culture and norms, and thus it is not surprising that it also permeates the professional-patient interaction [48]. In general, health systems in Spain are organized “for a culturally, linguistically and socially uniform population”, creating inequality in access and use of healthcare services [49].…”
Section: Discussionmentioning
confidence: 99%
“…Structural racism as manifest in ideologies, practices, processes and institutions that operate to produce and reproduce differential access to power [13] is deeply enrooted in social institutions, including the health system, its culture and norms, and thus it is not surprising that it also permeates the professional-patient interaction [48]. In general, health systems in Spain are organized “for a culturally, linguistically and socially uniform population”, creating inequality in access and use of healthcare services [49].…”
Section: Discussionmentioning
confidence: 99%
“…Our research showed that several participants were awaiting job assignments or had lower income (with some individuals even having a lack of income); thus, they were more vulnerable to poverty. Furthermore, the different social environment promoted different attitudes concerning sex-related behaviours [29, 30]. Some unmarried women felt embarrassed to discuss sexual matters, which is caused by traditional awareness, and did not seek help for RH problems.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, White, Ocampo, and Scarinci (2016) found culturally rooted concerns about oral contraceptives among recent Latina immigrants in the United States. Norms and preferences from the origin settings also influenced contraceptive choices of immigrants in Spain (Alvarez-Nieto et al 2015).…”
Section: Discussionmentioning
confidence: 99%